A Microporous Potassium‐Organic Framework for Efficient C2H2/CO2 Separation. Issue 22 (9th June 2022) - Guan, Haiyan; Zou, Shuixiang; Ji, Zhenyu; Li, Hengbo; Chen, Cheng; Wu, Mingyan
Abstract: A novel potassium‐based metal organic framework (TCBPA‐K ) was prepared by using a C3 ‐symmetric organic building block tris(4′‐carboxybiphenyl)amine (TCBPA). The compound has a rectangular like channel along the b axis and exhibits good selective adsorption performance. The single component gas adsorption isotherms indicated that the adsorption capacity of C2 H2 is much higher than that of CO2 at 298 K and 1 bar. The isosteric adsorption enthalpies of TCBPA‐K for C2 H2 and CO2 are 30.6 kJ/mol and 9.1 kJ/mol respectively. Ideal adsorbed solution theory calculation recorded the separation selectivity of C2 H2 /CO2 (50/50, v/v) as 3.5. Abstract : A novel potassium‐based metal organic framework with permanent 1D channel was prepared by using a C3 ‐symmetric organic linker. It has demonstrated a selective adsorption capacity for acetylene, which makes it possible to be a new C2 H2 /CO2 separation material.